Biomedical Applications of Hemicellulose-Based Hydrogels - Liu, Haitang; Chen, Ting; Dong, Cuihua; Pan, Xuejun (Current Medicinal Chemistry, 2020)
Background: Hydrogel has a three-dimensional network structure that is able to absorb a large amount of water/liquid and maintain its original structure. Hemicellulose (HC) is the second most abundant polysaccharide after cellulose in plants and a heterogeneous polysaccharide consisting of various saccharide units. The unique physical and chemical properties of hemicellulose make it a promising material for hydrogels. Methods: This review first summarizes the three research hotspots on the hemicellulose-based hydrogels: intelligence, biodegradability and biocompatibility. It also overviews the progress in the fabrication and applications of hemicellulose hydrogels in the drug delivery system and tissue engineering (articular cartilage, cell immobilization, and wound dressing). Results: Hemicellulose-based hydrogels have many unique properties, such as stimuliresponsibility, biodegradability and biocompatibility. Interpenetrating networking can endow appropriate mechanical properties to hydrogels. These properties make the hemicellulose-based hydrogels promising materials in biomedical applications such as drug delivery systems and tissue engineering (articular cartilage, cell immobilization, and wound dressing). Conclusion: Hydrogels have been widely used in biomedicine and tissue engineering areas, such as tissue fillers, drug release agents, enzyme encapsulation, protein electrophoresis, contact lenses, artificial plasma, artificial skin, and tissue engineering scaffold materials. This article reviews the recent progress in the fabrication and applications of hemicellulose-based hydrogels in the biomedical field.
Keywords: Intelligent hydrogel